2017
DOI: 10.4111/icu.2017.58.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of recurrence of overactive bladder symptoms after discontinuation of successful medical treatment

Abstract: PurposeTo identify incidence and risk factors of recurrence after discontinuation of successful antimuscarinic therapy in patients with overactive bladder (OAB).Materials and MethodsThis was a prospective, multicenter trial. Patients who had antimuscarinic agents for more than 12 weeks and showed successful response were enrolled. Successful response was defined as answering 'benefit' for patient perception of treatment benefit and answer lesser than 3 points in patient's perception of bladder condition (PPBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This result parallels similar findings of other studies conducted on OAB patients treated with antimuscarinics. For example, Kim et al found that OAB wet and female sex are independent risk factors after discontinuation of successful antimuscarinic treatment, Choo et al found that patients in the retreatment group had higher baseline urgency scores and were older than those seeking no further treatment, and a report from the UK found that patients who expressed beneficial effects of fesoterodine treatment showed a greater improvement after treatment and a greater deterioration after drug cessation than patients who did not respond positively . The present study has shown that patients resuming mirabegron had significantly more severe OAB symptoms at the time of mirabegron resumption than at the time of drug cessation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This result parallels similar findings of other studies conducted on OAB patients treated with antimuscarinics. For example, Kim et al found that OAB wet and female sex are independent risk factors after discontinuation of successful antimuscarinic treatment, Choo et al found that patients in the retreatment group had higher baseline urgency scores and were older than those seeking no further treatment, and a report from the UK found that patients who expressed beneficial effects of fesoterodine treatment showed a greater improvement after treatment and a greater deterioration after drug cessation than patients who did not respond positively . The present study has shown that patients resuming mirabegron had significantly more severe OAB symptoms at the time of mirabegron resumption than at the time of drug cessation.…”
Section: Discussionsupporting
confidence: 54%
“…Limited studies have examined the natural course of patients following the discontinuation of antimuscarinics once their symptoms have improved. Kim et al reported that 74.6%, 57.7%, and 47.8% patients had no recurrent OAB symptoms at 1, 3, and 6 months, respectively, after successful treatment (≥12 weeks) with antimuscarinics. Choo et al reported that approximately one‐third of OAB patients sought retreatment 1 month after discontinuation of antimuscarinic therapy following successful treatment with propiverine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al analyzed 371 participants that took antimuscarinic medication for a minimum of 12 weeks and had their symptoms subsided (35). The study stopped the treatment and viewed for symptom relapse for 1, 3, 6, and 12 months.…”
Section: Miko£aj Przydacz and Piotr Ch£ostamentioning
confidence: 99%
“…A recently-published study enrolled 371 OAB patients who took antimuscarinic agents for more than 12 weeks and responded favorably. 25 They then discontinued antimuscarinics and were evaluated for recurrence of bothering symptoms at baseline, 1, 3 and 6 months, with a limited number of patients followed up for 12 months. Cumulative recurrence rates at 1, 3 and 6 months were concurrent with earlier studies and were 25.6%, 42.3% and 52.2%, respectively.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%